# Question 6 - Examples - Chapter 4 Class 12 Determinants

Last updated at April 16, 2024 by Teachoo

Examples

Example 1

Example 2

Example 3

Example 4

Example 5 Important

Example 6

Example 7 Important

Example 8

Example 9

Example 10

Example 11 Important

Example 12

Example 13 Important

Example 14

Example 15 Important

Example 16

Example 17 Important

Example 18

Example 19 Important

Question 1

Question 2

Question 3

Question 4 Important

Question 5 Important

Question 6 You are here

Question 7

Question 8

Question 9 Important

Question 10 Important

Question 11 Important

Question 12

Question 13 Important

Question 14 Important

Question 15 Important

Chapter 4 Class 12 Determinants

Serial order wise

Last updated at April 16, 2024 by Teachoo

Question 6 Prove that |■8(𝑎&𝑎+𝑏&𝑎+𝑏+𝑐@2𝑎&3𝑎+2𝑏&4𝑎+3𝑏+2𝑐@3𝑎&6𝑎+3𝑏&10𝑎+6𝑏+3𝑐)| = a3 Let Δ = |■8(𝑎&𝑎+𝑏&𝑎+𝑏+𝑐@2𝑎&3𝑎+2𝑏&4𝑎+3𝑏+2𝑐@3𝑎&6𝑎+3𝑏&10𝑎+6𝑏+3𝑐)| Applying R2 → R2 – 2R1 = |■8(𝑎&𝑎+𝑏&𝑎+𝑏+𝑐@𝟐𝒂−𝟐(𝒂)&3𝑎+3𝑏−2(𝑎+𝑏)&4𝑎+3𝑏+2𝑐−2(𝑎+𝑏+𝑐)@3𝑎&6𝑎+3𝑏&10𝑎+6𝑏+3𝑐)| = |■8(𝑎&𝑎+𝑏&𝑎+𝑏+𝑐@𝟎&3𝑎+3𝑏−2𝑎−2𝑏&4𝑎+3𝑏+2𝑐−2𝑎−2𝑏−2𝑐@3𝑎&6𝑎+3𝑏&10𝑎+6𝑏+3𝑐)| = |■8(𝑎&𝑎+𝑏&𝑎+𝑏+𝑐@𝟎&𝑎&2𝑎+𝑏@3𝑎&6𝑎+3𝑏&10𝑎+6𝑏+3𝑐)| Applying R3 → R3 – 3R1 = |■8(𝑎&𝑎+𝑏&𝑎+𝑏+𝑐@0&𝑎&2𝑎+𝑏@𝟑𝒂−𝟑(𝒂)&6𝑎+3𝑏−3(𝑎+𝑏)&10𝑎+6𝑏+3𝑐−3𝑎+𝑏+𝑐)| = |■8(𝑎&𝑎+𝑏&𝑎+𝑏+𝑐@0&𝑎&2𝑎+𝑏@𝟎&6𝑎+3𝑏−3𝑎−3𝑏&10𝑎+6𝑏+3𝑐−3𝑎+𝑏+𝑐)| = |■8(𝑎&𝑎+𝑏&𝑎+𝑏+𝑐@0&𝑎&2𝑎+𝑏@0&3𝑎&7𝑎+3𝑏)| Expanding along C1 = = a |■8(𝑎&2𝑎+𝑏@3𝑎&7𝑎+3𝑏)| – 0 + 0 = a (a(7a + 3b) – 3a (2a + b) = a (7a2 + 3ab – 6a2 – 3ab) = a(a2) = a3 = R.H.S Hence proved |■8(𝑎&2𝑎+𝑏@3𝑎&7𝑎+3𝑏)| |■8(𝑎+𝑏&𝑎+𝑏+𝑐@3𝑎&7𝑎+3𝑏)|